2015
DOI: 10.1186/s40200-015-0133-6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biomarker N-acetyl-β-D-glucosaminidase can predict severity of renal damage in diabetic nephropathy

Abstract: BackgroundDiabetic nephropathy is a clinical diagnosis where proteinuria is present in a patient with diabetes. Early intervention can significantly improve the prognosis. However, imprecision of the currently available biomarkers have impaired effective therapies in a timely manner. Urinary N-acetyl-β-D-glucosaminidase (NAG) is excreted in abnormally high amounts in many renal diseases. The aim of this study was to evaluate urinary NAG as an early biomarker in detection of diabetic nephropathy and whether it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 32 publications
7
31
1
1
Order By: Relevance
“…It was already known that uNGAL/Cr and uNAG/Cr levels are significantly correlated with serum Cr [16,17]. In this study, a positive correlation was detected between uDA1/Cr levels and levels of serum Cr, which is a marker for kidney injury, among leptospirosis patients ( r = 0.3; p < 0.01) (Figure 2A).…”
Section: Resultssupporting
confidence: 64%
“…It was already known that uNGAL/Cr and uNAG/Cr levels are significantly correlated with serum Cr [16,17]. In this study, a positive correlation was detected between uDA1/Cr levels and levels of serum Cr, which is a marker for kidney injury, among leptospirosis patients ( r = 0.3; p < 0.01) (Figure 2A).…”
Section: Resultssupporting
confidence: 64%
“…A more recent study found that urinary NAG was significantly higher in type 2 diabetic patients with normo-, micro- and macroalbuminuria than in non diabetic controls, and its value increased in parallel with the severity of renal involvement. Significant positive correlation was observed between urinary NAG and ACR, SCr and HbA1c, suggesting that urinary NAG could be used as a useful biomarker reflecting the degree of renal impairment in DN [ 18 ]. Another study showed that urinary NAG levels were significantly increased in microalbuminuria group compared to normoalbuminuria group and correlated positively with ACR, indicating the possible clinical application of urinary NAG as a complementary marker for early detection of DN in type 2 diabetes [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown only that urinary NAG excretion gradually increases with increases in duration of diabetes, [ 13 ] fasting plasma glucose levels, [ 14 ] or hemoglobin A 1c (HbA 1c ) levels. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%